Quercetin Induces Apoptosis Through Downregulating P4HA2 and Inhibiting the PI3K/Akt/mTOR Axis in Hepatocellular Carcinoma Cells: An In Vitro Study - Junli Zhang; Jiayi Guo; Ying Qian; Lianchen Yu; Junrao Ma; Biao Gu; Weichun Tang; Yi Li; Hongwei Li; Wenjuan Wu (Cancer Reports)
ABSTRACT Background Quercetin is a natural product with multiple activities, which possesses a promising antitumor effect on malignancies. The involvement of proline 4‐hydroxylase II (P4HA2) in collagen synthesis is crucial in the growth of tumor cells. Apoptosis is a programmed cell death requisite for the stability of the intracellular environment. However, the relationship between quercetin and cell apoptosis, as well as the impact of P4HA2 in this connection, has not yet been specified in hepatocellular carcinoma(HCC). Aims The present study used HCC cells to investigate how quercetin regulates P4HA2 and influences cell proliferation and apoptosis. Methods and Results The outcomes reveal that quercetin can impede the viability and growth of HCC cells and generate cell apoptosis in a dose‐dependent manner. Additionally, quercetin prompts downregulation of P4HA2, leading to cell apoptosis in HCC cells, and knocking down P4HA2 can enhance this effect. Furthermore, we pretreated HCC cells with inhibitors (Z‐VAD‐FMK, LY294002) or activators (740Y‐P) and found that the PI3K/Akt/mTOR pathway was occupied with quercetin‐induced cell apoptosis. Conclusion This investigation reveals that quercetin compels apoptosis in HCC cells by diminishing P4HA2 and restraining the PI3K/Akt/mTOR axis.